Transfemoral transcatheter aortic valve replacement compared with surgical replacement in patients with severe aortic stenosis and comparable risk: Cost–utility and its determinants. (1st March 2015) - Ribera, Aida; Slof, John; Andrea, Rut; Falces, Carlos; Gutiérrez, Enrique; del Valle-Fernández, Raquel; Morís-de la Tassa, César; Mota, Pedro; Oteo, Juan Francisco; Cascant, Purificació; Altisent, Omar Abdul-Jawad; Sureda, Carlos; et al.
Abstract: Objective: To evaluate cost-effectiveness of transfemoral TAVR vs surgical replacement (SAVR) and its determinants in patients with severe symptomatic aortic stenosis and comparable risk. Methods: Patients were prospectively recruited in 6 Spanish hospitals and followed up over one year. We estimated adjusted incremental cost-effectiveness ratio (ICER) (Euros per quality-adjusted life-year [QALY] gained) using a net-benefit approach and assessed the determinants of incremental net-benefit of TAVR vs SAVR. Results: We analyzed data on 207 patients: 58, 87 and 62 in the Edwards SAPIEN (ES) TAVR, Medtronic-CoreValve (MC) TAVR and SAVR groups respectively. Average cost per patient of ES-TAVR was €8800 higher than SAVR and the gain in QALY was 0.036. The ICER was €148, 525/QALY. The cost of MC-TAVR was €9729 higher than SAVR and the QALY difference was − 0.011 (dominated). Results substantially changed in the following conditions: 1) in patients with high preoperative serum creatinine the ICERs were €18, 302/QALY and €179, 618/QALY for ES and MC-TAVR respectively; 2) a 30% reduction in the cost of TAVR devices decreased the ICER for ES-TAVR to €32, 955/QALY; and 3) imputing hospitalization costs from other European countries leads to TAVR being dominant. Conclusions: In countries with relatively low health care costs TAVR is not likely to be cost-effective compared to SAVR in patients with intermediate risk for surgery, mainly because of the high cost of the valve compared to the cost of hospitalization. TAVR could be cost-effective in specific subgroups and in countries with higher hospitalization costs.